The Application of Human Organization Technology Model to Evaluate ERP Information Systems in General Contractor, Supplier and Trade National Companies - Senoaji, Fauzie; Nuraeni, Lenny; Suwarna, A Idun; Safrida, Safrida; Sriyono, Sriyono (Institut Riset dan Publikasi Indonesia, 2024)
The goal of this study is to assess the system and identify the key performance indicators for the enterprise resource planning (ERP) information system. Researchers also spoke with a number of respondents in unstructured interviews; the results of these interviews served as some supporting information on the business. Saturated sampling combined with a nonprobability sampling strategy was employed by researchers. Thus, 100 respondents, or samples, were used in this study. To create the framework for the research model that would be utilized, research model creation was done. The HOT Fit model was employed in this study. There are four hypotheses that cannot be accepted, according to the study and discussion outcomes. System usage, user satisfaction, structure, and environment are the aspects that affect net benefit; system quality, information quality, and service quality are the factors that influence system use, user satisfaction, and structure. In this study, the variable relationship with the highest influence is IQ? US, with a path coefficient value of 0.5, and the variable relationship with the lowest value is SU? NB, with a route coefficient value of 0.1. Thirteen of the hypotheses are accepted, whereas two have little bearing.